Atenção às urgências odontológicas em unidades de pronto-atendimento do sistema único de saúde - Rios, Leonardo Essado (2013)
The pain of dental origin has high prevalence, presents itself as a public health problem and cause negative impact on quality of life of people. Because of that, attention to dental emergencies has particular importance in the health care of the population, however there is little research on this topic. In the present study it was aimed to analyze dental care in Emergency Care Units of the Unified Health System (SUS) in optics of dentists workers in this service. It was a study of mixed methods and data were collected through a questionnaire with assertions of polar agreement and disagreement (Likert scale). Participated as subjects dentists (N = 44) workers in the emergency dental service of the Emergency Care Units of SUS from Goiânia, GO. There was a tendency to full concordance (average percentage of agreement above 76%) about this type of service answering to a spontaneous demand with complaints of pain and trauma and also about the affirmation that basic procedures of urgency such as dental extractions, alveolitis and bleeding treatments, drainage of intraoral abscesses and medicalization must be performed there. Tendency to concordance (average percentage between 26% and 75%) was verified in relation to the statement that the service aims to relief the suffering of the population with pain of dental origin. Propensity to indifference (average percentage among -25% and 25%) occurred on the host with risk classification while service feature, and still about patients that should be referred to more complex units for emergency care. Tendency to disagreement (average percentage among -26% and -75%) was verified in relation to the attendance of non-urgent patients and the performance of dental restorative procedures. There was no tendency to full disagreement (average percentage above -75%) about any of the items. In the view of respondents the emergency dental care in emergency units of SUS are intended for the relief of typically urgent situations, in cases where there is no risk of advanced infections, by performance of procedures characteristically related to situations of urgency and that require basic technical fitness from the professional. There’s a lack on the policy of humanization and teamwork at the service. As a product of the study, it was designed a proposal for an update course of dental care to the professionals in the Emergency Care Units.